Easy Handling Preparation of Cubic Sulfur in Aqueous Extract of Sapindus rarak rinds - Charles Banon; Nesbah Nesbah; Bambang Trihadi; Aswin Falahudin; Salprima Yudha S (Molekul, 2022)
The aqueous extract of Sapindus rarak (S. rarak) was produced by heating its rinds in demineralized water at 80 °C. The main experiment was conducted at room temperature by mixing a solution of sodium thiosulfate with the extract obtained previously. After adding dilute hydrochloric acid (10%), fine granules gradually formed in the solution and precipitated when the reaction was stopped and allowed to stand for 24 h. The analysis results showed the consistency of the X-ray diffraction (XRD) peak of the obtained material with sulfur standards. When looked at the surface using scanning electron microscopy (SEM), sulfur was found to be cube-shaped. The formation of cuboidal elemental sulfur possibly occurs due to the covering of thiosulfate ions and elemental sulfur during and after the reaction. Organic compounds were found covering sulfur through elemental and functional group analyses using energy-dispersive X-ray (EDX) and Fourier-transform infrared (FTIR) spectroscopy, respectively